The Response of Extracellular Polymeric Substances Production by Phototrophic Biofilms to a Sequential Disturbance Strongly Depends on Environmental Conditions - Loustau, Emilie; Leflaive, Joséphine; Boscus, Claire; Amalric, Quentin; Ferriol, Jessica; Oleinikova, Olga; Pokrovsky, Oleg S.; Girbal-Neuhauser, Elisabeth; Rols, Jean-Luc (Frontiers in Microbiology, 2021)
In a context of climate change associated with anthropic pressures, phototrophic biofilms are exposed to multiple stressors, either simultaneously or sequentially. Press stressors, like warming or nutrient increase, can affect the biofilms directly, but also in a more discreet way. By modifying either the composition of the community or the physiology of the microorganisms, they may indirectly impact the ability of the biofilms to cope with another disturbance. The aim of this study was to decipher in what extent a slight modification of environmental conditions could alter the response of biofilms to a realistic sequential disturbance. By using very simplified biofilms (one algal strain plus the associated bacteria), we only considered physiological effects. We focused on the extracellular polymeric substances (EPS) produced by the biofilms, since they are supposed to play an important role in the resistance of biofilms to various stresses. An experiment with artificial streams was performed during 46 days with two simplified biofilms composed by a green alga (Uronema confervicolum) or a diatom (Nitzschia palea) and the associated bacteria, and grown in six different conditions of light intensity, temperature and phosphorous concentration. The combined effects of Cu exposure (50 µg L-1 during 4 days) followed by drought (14 days) were evaluated immediately at the end of the disturbance and after a 14-day rewetting period. The environmental factors strongly impacted the growth and photosynthetic efficiency of the biofilms, and the EPS quantity and quality (ratio between proteins and polysaccharides), with contrasted effects on the two biofilms. The response of the EPS to the disturbance was also dependent on the pre-disturbance conditions, and on the algal species. For instance, for EPS production, warming increased the impact of the disturbance in the diatom biofilm, and a high phosphorous concentration decreased the resilience in the green alga biofilm. Moreover, some factors that had no effects on EPS before the disturbance were able to modify the response to the disturbance. These results highlight the importance of considering not only the direct effects of global change on the microbial communities, but also its indirect effects on the response of communities to additional disturbances.